2015
DOI: 10.1021/acs.jmedchem.5b00606
|View full text |Cite
|
Sign up to set email alerts
|

Original 2-(3-Alkoxy-1H-pyrazol-1-yl)azines Inhibitors of Human Dihydroorotate Dehydrogenase (DHODH)

Abstract: Following our discovery of human dihydroorotate dehydrogenase (DHODH) inhibition by 2-(3-alkoxy-1H-pyrazol-1-yl)pyrimidine derivatives as well as 2-(4-benzyl-3-ethoxy-5-methyl-1H-pyrazol-1-yl)-5-methylpyridine, we describe here the syntheses and evaluation of an array of azine-bearing analogues. As in our previous report, the structure–activity study of this series of human DHODH inhibitors was based on a phenotypic assay measuring measles virus replication. Among other inhibitors, this round of syntheses and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 67 publications
0
31
0
Order By: Relevance
“…Most importantly, we characterized in detail the interactions between this new series of pyrimidine biosynthesis inhibitors, which were identified in an ISRE-luciferase screen, and the innate antiviral response. It has been previously shown that pyrimidine biosynthesis inhibitors are weak stimulators of ISGs when applied alone ( 8 , 13 18 ), but these drugs boost the expression of ISGs in response to either extracellular or intracellular stimuli, such as IFN-β, RIG-I ligands, or viruses ( 8 , 12 , 13 , 15 , 18 ). Besides, pyrimidine biosynthesis inhibitors do not induce any type of IFNs when applied alone, and virus growth inhibition by these drugs seems to occur independent of IFN-α/β synthesis ( 8 , 15 , 16 ), despite some recent report showing no antiviral effects in Vero cells which are deleted for the IFN-α/β gene cluster ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most importantly, we characterized in detail the interactions between this new series of pyrimidine biosynthesis inhibitors, which were identified in an ISRE-luciferase screen, and the innate antiviral response. It has been previously shown that pyrimidine biosynthesis inhibitors are weak stimulators of ISGs when applied alone ( 8 , 13 18 ), but these drugs boost the expression of ISGs in response to either extracellular or intracellular stimuli, such as IFN-β, RIG-I ligands, or viruses ( 8 , 12 , 13 , 15 , 18 ). Besides, pyrimidine biosynthesis inhibitors do not induce any type of IFNs when applied alone, and virus growth inhibition by these drugs seems to occur independent of IFN-α/β synthesis ( 8 , 15 , 16 ), despite some recent report showing no antiviral effects in Vero cells which are deleted for the IFN-α/β gene cluster ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The T7 transcription start is located 36 nucleotides upstream of the Xba1 restriction site, but runoff transcription in vitro is known for producing at a high yield longer 5′-triphosphate RNA molecules that include copy-back sequences and fold into stem-loop structures ( 33 ). Such ssRNA molecules were previously shown to efficiently stimulate the interferon response by the RIG-I/MAVS pathway when transfected in HEK-293 or STING-37 cells ( 8 , 12 , 22 , 34 ). For each production lot, pools of in vitro transcripts were purified with a filtering membrane (SEQ96 sequencing reaction cleanup; Millipore), analyzed on a Bioanalyzer RNA Nano kit (Agilent), and qualified for their immunostimulatory properties on STING-37 reporter cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ribavirin and uridine were from Sigma-Aldrich. IPPA17-A04 and GAC50 were previously described and kindly provided by Dr. Yves Janin (Institut Pasteur, Paris, France) and Dr. Daniel Dauzonne (Institut Curie, Paris, France), respectively 25-27 . Ribavirin was dissolved in PBS buffer and uridine in sterile water, whereas IPPA17-A04 and GAC50 were dissolved in DMSO.…”
Section: Methodsmentioning
confidence: 99%
“…Besides ribavirin, we also tested two newly designed BSA that target the pyrimidine biosynthesis pathway, namely GAC50 and IPPA17-A04. These two molecules are inhibitors of dihydroorotate dehydrogenase (DHODH), the fourth and rate-limiting enzyme of the de novo pyrimidine biosynthesis pathway, and were shown to impair the replication of many different positive-strand and negative-strand RNA viruses 25-27 . In this study, we have shown, for the first time, that both ribavirin and pyrimidine biosynthesis inhibitors inhibit EAV in equine dermal cell cultures.…”
Section: Introductionmentioning
confidence: 99%